What Kinds of Cosmetic Appearances were Improved after Scoliosis Surgery in Adolescent Idiopathic Patients? A Longitudinal Long-term Postoperative 7-year Study Using Spinal Appearance Questionnaire - Wai-Wang Chau; Bobby Kin-Wah Ng (Journal of Orthopedics and Joint Surgery)
Background and aim: The primary purpose of spinal corrective surgery is to prevent scoliosis progression by spinal fusion at the regions of involvement. Patients would like to see corrections on their trunk appearance along with the spinal correction. Long-term longitudinal follow-up of cosmetic trunk appearance in surgical adolescent idiopathic scoliosis (AIS) patients using solely an appearance-specific questionnaire has not yet been reported. Materials and methods: All severe AIS patients operated on from the year 2014 to 2016 were recruited. They completed a spinal appearance questionnaire (SAQ) at a time point from <1 year to 6–7 years after surgery (7 time points). Spinal appearance questionnaire domain scores from the 7 time points were compared using ANOVA with multiple comparison corrections. Results: There were 76 severe AIS patients recruited, of which 74.1% were females, and the mean age at operation was 15.97. Mean”General,” “Waist,” and “Chest” SAQ domain scores were consistently scored high across the 7 time points. The “surgical scars” domain consistently scored the lowest among the nine SAQ domains. Female patients observed significantly better mean “Curve” and “Trunk shift” domain scores at 4–6 years compared with <2 years despite none found in male patients. Conclusion: Postoperative AIS patients were highly satisfied with their general appearance, waist, and chest 7 years after surgery. “Surgical scars” was persistently the least satisfied domain across the 7 years after surgery. Gender difference existed of which female patients felt significantly better on their “curves” and “trunk shift” after 4 years of surgery but the significance was not found in male patients.